Synthesis and Crystal Structure of 6-Ethoxy-4’,6’-dibromo-2,2’-[ethylenedioxybis(nitrilomethylidyne)]diphenol - Liu, Xin-Wen; Wu, Jun-Jiang; Zhang, Yu-Jie; Li, Gang; Wang, Li; Dong, Xiu-Yan (Asian Journal of Chemistry, 2013)
The title compound, 6-ethoxy-4',6'-dibromo-2,2'-[ethylenedioxybis(nitrilomethylidyne)]diphenol with the molecular formula C18H18Br2N2O5, adopts an L-shaped configuration, in which the benzene units are approximately perpendicular, making a dihedral angle of 76.39(3)º. Intramolecular H-bonds are formed between the OH groups and the N atoms. In the crystal structure, each molecule links other molecules into an infinite three-dimensional supramolecular structure by intermolecular C-H···O and C-H···p hydrogen bond interactions.